Epidemiological Profile of Breast Cancer Phenotypes in Rural Southern West Bengal, India - Chaudhury, Arindam; Santhyavu, Sanjay; Mallik, Mandira Saha; Gupta, Kushal; Mishra, Shalini; Ghosh, Arnab Kumar; Dandapat, Adhiraj (Asian Pacific Journal of Cancer Care, 2025)
Background: Breast cancer (BC) is now the most common cancer globally, exceeding lung cancer in 2020 with 2.3 million new cases. In 2016, India had an estimated 118,000 new cases, with a 39.1% increase in the age-standardized incidence rate between 1990 and 2016. This abstract highlights the growing global burden of BC, particularly focusing on the increasing incidence in rural India. Methods: A retrospective, observational study was conducted at the Department of Radiation Oncology, All India Institute of Medical Sciences, Kalyani, focusing on rural areas in southern West Bengal between July 2022 and January 2025 in women with biopsy-proven breast cancer. The data of the patients pertaining to histopathology, hormone status, Grade of tumour, Ki-67 Index, and demography were collected, and phenotypical classification was derived. Results: Among 456 breast cancer patients (159 premenopausal, 297 postmenopausal), 58.1% had locally advanced disease. Most presented with grade III tumours (51.8%) and high Ki-67 (67.9%). Infiltrating ductal carcinoma was predominant. Hormone receptor positivity was higher in premenopausal (64.77%) vs postmenopausal (52.52%) women; HER2 neu negative cases were more common in postmenopausal women (67.33%). Predominant phenotypic subgroups: premenopausal luminal B (40.9%), postmenopausal luminal A (34%). Interpretation and Conclusion: The findings suggest the need for tailored therapeutic strategies, especially considering the distinct phenotypic subgroups identified. Overall, these insights contribute to a better understanding of breast cancer’s epidemiology and may inform future treatment approaches and research directions in this area.